BUDAYA PATRIARKHI DAN PERJUANGAN PEREMPUAN DALAM NOVEL PESAN CINTA DARI HUJAN KARYA ERNI ALADJAI - MUH RAFI'I (JURNAL PENDIDIKAN GLASSER, 2018)
This paper discusses patriarchy culture and women’s struggles in Pesan Cinta Dari Hujan, a novel written by Erni Aladjai (2010). Patriarchy culture can be seen in attitudes, behaviors, and actions conducted by male characters toward female characters. This paper adopts a feminist approach to explore patriarchy culture and women’s struggles in the novel. The findings show that patriarchy culture includes violence of domestic or women, violence of education and building children’s characters, and violence of space and movement given for self-actualization. Women characters’ struggles to fight patriarchy culture are determination, tear, and running..